Processes of Ethnic Identity Formation among Descendants of Immigrants: The Case of the Communities of Buenos Aires and the Misiones Province (Argentina) - Porada, Katarzyna (2017)
Polish community in Argentina –along with the community in Brazil– is one of the most numerous Polishorigin communities in Latin America. Seventy years have passed since the migratory processes between Poland and Argentina practically came to a halt, and the temporal distance since the arrival of the last group of Poles to this country is now reflected in the gradual and inevitable disappearance of the majority of these immigrants. Today, their adult descendants, who were born (many in exogamic families), raised and educated in Argentina, continue with a variety of activities that attempt, in one way or another, to keep the Polish culture alive. These activities, however, do not take shape in a vacuum or independently from the context surrounding particular groups; on the contrary, they are constructed in constant interaction with the receiving society and with the rest of the groups. In this article, based on the specific case of the Polish community in Buenos Aires and in the Misiones Province (Argentina), we intend to analyze the particularities.